The Impact of Operational Profitability and Asset Growth on Company Value With Debt Structure as a Moderating Variable - Anggi Ayuni Dewi; Diah Nur Cahyati; Golda Kusuma Akbar Sihite; Karolina Boromensa Baitanu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of operational profitability and asset growth on firm value and to examine the role of capital structure as a moderating variable. The research sample consists of 26 transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, with a total of 130 observations. The analytical methods employed are multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that operational profitability and asset growth do not have a significant effect on firm value. The moderation analysis shows that capital structure moderates the relationship between operational profitability and firm value with a weakening effect, while it does not moderate the relationship between asset growth and firm value. Meanwhile, the simultaneous test results reveal that operational profitability and asset growth jointly have a significant effect on firm value. This study emphasizes that firm value is influenced by the combination of financial performance and an optimally managed capital structure.